Efektivitas Penggunaan Alat Kontrasepsi Sebagai Upaya Pencegahan Stunting - Khobibah Khobibah; Septalia Isharyanti; Heny Rosiana (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
Stunting was the condition of growth failure experienced the children aged under 5 years, which was caused the lack of nutrition. Stunting related with the increasing the risk of morbidity, mortality and inhibition ofÂ motoric and mental the children. The research was analytic study, case control retrospektif design with total sample 102 respondents. The data analisa used Chi Square. The results showed that there was no correlation between the parity with the incidence of stunting (p value = 1,000 > 0,05), no correlation between the pregnancy spacing with the incidence of stuntingÂ (p value = 1,000 > 0,05) and no correlation between the use of contraception with incidence of stunting (p value = 0,787 > 0,05). Recommendation for further research to expand the area and look for other factors that influence the incidence of stunting.